IMPLICATION OF INORGANIC CHEMISTRY ON THE ENVIRONMENT (International Journal of Food and Nutritional Sciences, 2022)
Direct and selective replacement of carbon-hydrogen bonds with new bonds (such as C–C, C–O, and C–N) represents an important and long-standing goal in chemistry. These transformations have broad potential in synthesis because C–H bonds are ubiquitous in organic substances. At the same time, achieving selectivity among many different C–H bonds remains a challenge. Here, we focus on the functionalization of C–H bonds in complex organic substrates catalyzed by transition metal catalysts. We outline the key concepts and approaches aimed at achieving selectivity in complex settings and discuss the impact these reactions have on synthetic planning and strategy in organic synthesis.